PENGARUH LUAS LAHAN, CURAHAN TENAGA KERJA DAN BIAYA PRODUKSI TERHADAP PENDAPATAN USAHATANI BAWANG MERAH DI KABUPATEN BOJONEGORO - Retna Dewi Lestari; Nastiti Winahyu (Journal Science Innovation and Technology (SINTECH), 2021)
Horticulture development is one of the strategic issues in increasing the role of agriculture in the national economy in 2020-2024. One of the potential horticultural commodities is shallot. One of the areas in East Java that is developing intensive shallot cultivation is Bojonegoro Regency. The characteristic of shallot cultivation is that it requires more intense care than other horticultural cultivations, including the care and control of pests. The existence of intense care in the cultivation of shallots results in the need for quite a lot of labor, so that the care and maintenance is optimal. The labor used will affect the income of shallot farmers. The use of intensive care inputs such as fertilizers and pesticides will also affect the costs and income of shallot farmers. The purpose of this study was to examine whether land area, labor expenditure, and production costs will affect the income of onion farming in Bojonegoro Regency. The results showed that the outpouring of labor and production costs had a significant effect on farmers' income on onion farming in Bojonegoro Regency.